The Role of Palestinian Olympic Committee in Crises Management According to Individual Sport Unions During Corona Pandemic - Nada, Ala' Majed Huseen; Ghrab, Hatem; Dabeek, Qasem Assad; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
This study aimed to identify the role of the Palestinian Olympic Committee in managing crises from the point of view of individual sports federations in light of the Corona pandemic, as well as to identify the differences in the role of the Palestinian Olympic Committee in managing crises from the point of view of individual sports federations in light of the Corona pandemic, according to variables (gender, characteristic Management, academic qualification, years of experience). The descriptive analytical method was used in one of the forms of the survey study due to its suitability for the purposes of the study. The study sample consisted of (90) administrative members of sports federations, selected by a random-stratified method. The questionnaire was also used as a tool for the study. The results of the study showed that the total degree of the role of the Palestinian Olympic Committee in crisis management from the point of view of sports federations was moderate with an average of (2.99),The results also showed that there are no statistically significant differences at the significance level (α ≤ 0.05) in the role of the Palestinian Olympic Committee in crisis management from the point of view of individual sports federations, in the total degree ,before the crisis occurred and during the crisis) due to For the gender . On the other hand, differences were statistically significant in (after the crisis occurred) due to gender and in favor of females. The results showed that there were no statistically significant differences due to characteristic Management, academic qualification, years of experience variables.